Power Up: Lessons Learned from World's Utility Landscape (International Journal of Engineering Management Science, 2023)
The United States utility sector faces pressing challenges related to the aging infrastructure, evolving energy demands, and sustainability goals. This article explores how successful international utility models can guide the U.S. in modernizing its energy systems. By examining case studies from Germany, the UK, Denmark, South Korea, and Japan, we identify key strategies in innovation, customer choice, renewable energy integration, smart grid technologies, and regulatory frameworks. Germany’s Energiewende and Denmark’s wind energy initiatives highlight effective policies and technical measures for renewable energy integration. South Korea and Japan have showcased advancements in smart grid technologies that improve efficiency and reliability. This article advocates the adoption of utility model legislation, fostering competition, investing in renewable energy, and upgrading grid infrastructure. Lessons from global best practices offer a roadmap for U.S. utilities to achieve a more sustainable, efficient, and resilient energy future.
Keywords: Utility Models, Energy Modernization, Renewable Energy, Smart Grid Technologies, Regulatory Frameworks, International Case Studies, Germany’s Energiewende, Denmark Wind Energy, South Korea Smart Grid, Japan Advanced Metering